DiscussionsCategory: MathematicsPlease Simplify -2 [a – 2] = -3 [ b – 4 ]

Please simplify -2 [a – 2] = -3 [ b – 4 ]

-2xa – 2x-2= -3xb – 3x-4
-2a+4= -3b+12
Collect like term
-2a+3b=12-4
3b-2a=8

-2a + 3b – 8 = 0;
Or -a2 + 3b = 8

-2[a – 2] = -3[b – 4]
Clear the bracket by multiplying LHS by -2 and RHS by -3:
-2a + 4 = -3b + 12
Collect like terms
-2a + 3b = 12 – 4
-2a + 3b = 8

-2[a – 2] = -3[b – 4]
-2a + 4 = -3b + 12
-2a + 3b = 12 – 4
-2a + 3b = 8…….(i)  to prove that this is true
Let find the value of a and substitute in (i) above
-2a + 3b = 8
-2a = 8 – 3b
a = [8 – 3b] / -2
Substituting (a) in (i) we have
-2a + 3b = 8
-2[(8 – 3b)/ -2] + 3b = 8
8 – 3b + 3b = 8
8 = 8
Therefore, it is true that -2a + 3b = 8

= – 2a + 3b = 8

-2(a-2)=-3(b-4)
=-2a+4=-3b+12
=-2a+3b=12-4
=-2a+3b=8

-2a+3b=8

-2(a-2)=-3(b-4)
Solution
-2(a-2)=-3(b-4)
-2a+4=-3b+12
Collect like terms
When minus(-) cross over it turns plus while when plus(+) crosses over it turns minus sign
-2a+3b=12-4
-2a+3b=8
Take note
+ × – = –
– × + = –
+ × + = +
– × – = +
So you use -2 to multiply your first bracket and use -3 bracket is multiplication because its in bracket cause you are using the number before the bracket to multiply all numbers in the bracket each like if you put the equation
-2×a-2=-3×b-4you get
-2a-2=-3b-4 because there is no bracket.